Perceptions of the Appropriateness of the Procedures to Develop Quality Assurance Mechanisms to Foster Tanzanian Universities’ Compliance - Mrema, Daudi; Ndayambaje, Irénée; Ntawiha, Philothère; Ndabaga, Eugene (International Journal of African Higher Education, 2024)
Contemporary external and internal quality assurance structures employ participatory procedures to design quality assurance mechanisms that promote universities’ compliance. Tanzania is among the countries that have adopted such measures to promote key stakeholders’ acceptance and implementation. This study explored Tanzanian stakeholders’ perceptions of the appropriateness of the procedures that guide the development of national and institutional quality assurance mechanisms to foster universities’ compliance. Data were gathered from 46 participants across four universities by means of interviews, focus group discussions and documentary review. The data were analysed using content analysis. The analysis revealed that some key stakeholders did not make sufficient input into existing quality assurance mechanisms, resulting in non-compliance among universities, academics and students. Recommendations are offered to increase key stakeholders’ involvement and thus enhance compliance.